Property Development - Reed, Richard. 1963- (Routledge/Taylor & Francis Group, 2021)
"This fully revised 7th edition of Property Development has been completely updated to reflect ongoing changes in the property field and maintain the direct relevance of the text to all stakeholders involved in studying the property development process"--